Optimal Approach and Strategies to Strengthen Pharmacovigilance in Sub-Saharan Africa: A Cohort Study of Patients Treated with First-Line Artemisinin-Based Combination Therapies in the Nanoro Health and Demographic Surveillance System, Burkina Faso - Rouamba T; Sondo P; Derra K; Nakanabo-Diallo S; Bihoun B; Rouamba E; Tarnagda Z; Kazienga A; Valea I; Sorgho H; Pagnoni F; Samadoulougou-Kirakoya F; et al. (Dove Medical Press, 2020)
Toussaint Rouamba,1,2 Paul Sondo,1 Karim Derra,1 Seydou Nakanabo-Diallo,1,3 Biebo Bihoun,1 Eli Rouamba,1 Zekiba Tarnagda,1 Adama Kazienga,1 Innocent Valea,1 Hermann Sorgho,1 Franco Pagnoni,4 Fati Samadoulougou-Kirakoya,2 Halidou Tinto1 1Clinical Research Unit of Nanoro, Institut de Recherche en Sciences de la Santé, Centre National de la Recherche Scientifique et Technologique, Ouagadougou, Burkina Faso; 2Center for Research in Epidemiology, Biostatistics and Clinical Research, School of Public Health, Université Libre de Bruxelles (ULB), Bruxelles, Belgium; 3Department of Clinical Research, Centre Muraz, Bobo-Dioulasso, Burkina Faso; 4World Health Organization, Geneva, SwitzerlandCorrespondence: Toussaint RouambaClinical Research Unit of Nanoro, Institut de Recherche en Sciences de la Santé, Centre National de la Recherche Scientifique et Technologique, 42, Avenue Kumda-Yonre, 11 BP 218 Ouaga CMS 11, Ouagadougou, Burkina FasoTel +226 6665 3204Email rouambatoussaint@gmail.comBackground and purpose: Resource-limited countries face challenges in setting up effective pharmacovigilance systems. This study aimed to monitor the occurrence of adverse events (AEs) after the use of artemisinin-based combination therapies (ACTs), identify potential drivers of reporting suspected adverse drug reactions (ADRs) and monitor AEs among women who were inadvertently exposed to ACTs in the first trimester of pregnancy.Patients and methods: We conducted a prospective observational study from May 2010 to July 2012 in Nanoro Health and Demographic Surveillance System (HDSS), Burkina Faso. The HDSS area was divided into active and passive surveillance areas to monitor AEs among patients (regardless of age or sex) who received a first-line ACT (artemether–lumefantrine or artesunate–amodiaquine). In the active surveillance area, patients were followed up for 28 days, while in the passive surveillance area, patients were encouraged to return voluntarily to the health facility to report any occurrence of AEs until day  28 after drug intake. We assessed the crude incidence rates of AEs in both cohorts and performed Cox regression with mixed random effects to identify potential drivers of ADR occurrence.Results: In total, 3170 participants were included in the study. Of these, 40.3% had reported at least one AE, with 39.6% and 44.4% from active and passive surveillance groups, respectively. The types of ADRs were similar in both groups. The most frequent reported ADRs were anorexia, weakness, cough, dizziness and pruritus. One case of abortion and eight cases of death were reported, but none of them was related to the ACT. The variance in random factors showed a high variability of ADR occurrence between patients in both groups, whereas variability between health facilities was low in the active surveillance group and high in passive surveillance group. Taking more than two concomitant medications was associated with high hazard in ADR occurrence, whereas the rainy season was associated with low hazard.Conclusion: This study showed that both passive and active surveillance approaches were useful tools. The HDSS allowed us to capture a few cases of exposure during the first trimester of pregnancy. The passive surveillance approach, which is more likely to be implemented by malaria control programs, seems to be more relevant in the Sub-Saharan African context.Keywords: HDSS, artemisinin-based combination therapies, safety, pregnancy, malaria, rural, Burkina Faso